2021
DOI: 10.1109/lcomm.2021.3100347
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic Rate Analysis and IRS Configuration for Multi-IRS Dual-Hop DF Relaying Systems

Abstract: Intelligent reflecting surface (IRS) has emerged as a promising and low-cost technology for improving wireless communications by collecting dispersed radio waves and redirecting them to the intended receivers. In this letter, we characterize the achievable rate when multiple IRSs are utilized in the manner of decode-and-forward (DF) relaying. Our performance analysis is based on the Nakagami-m fading model with perfect channel state information (CSI). Tight upper bound expressions for the ergodic rate are deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…We derive closed-form expressions for the achievable rates for two NOMA users under the channel models of Rayleigh and Rician. Compared with recent work [30], our result could be combined with their result to provide complete ergodic performance analysis in a more practical circumstance.…”
mentioning
confidence: 85%
“…We derive closed-form expressions for the achievable rates for two NOMA users under the channel models of Rayleigh and Rician. Compared with recent work [30], our result could be combined with their result to provide complete ergodic performance analysis in a more practical circumstance.…”
mentioning
confidence: 85%
“…Moreover, the authors in [29] studied the deployment strategy in RIS-assised relaying system, and showed that the multi-RIS relaying system attains a higher capacity order. In [30], a multi-RIS relaying system in Nakagami-m fading channels was investigated, where closed-form expressions are derived for the upper bound on the ergodic capacity. In [31], a deep reinforcement learning algorithm was proposed to design the relay selection scheme in RIS-assisted cooperative networks, which was shown to achieve significant performance gains as compared to random relay selection and random passive beamforming designs.…”
Section: Introductionmentioning
confidence: 99%
“…It proved that the rate performance of the proposed new system is better than that of the conventional IRS without relaying. The authors proposed a multi-IRS-aided DF relay network [24], where the IRS configuration including the numbers of IRSs and IRS reflecting elements was considered to maximize the rate. For a given channel coherence time, it was indicated that fewer IRSs with a larger number of reflecting elements tend to have better rate performance.…”
mentioning
confidence: 99%